1998
DOI: 10.1093/jn/128.10.1643
|View full text |Cite
|
Sign up to set email alerts
|

Protein Deficiency and Nutritional Recovery Modulate Insulin Secretion and the Early Steps of Insulin Action in Rats

Abstract: Maternal malnutrition was shown to affect early growth and leads to permanent alterations in insulin secretion and sensitivity of offspring. In addition, epidemiological studies showed an association between low birth weight and glucose intolerance in adult life. To understand these interactions better, we investigated the insulin secretion by isolated islets and the early events related to insulin action in the hind-limb muscle of adult rats fed a diet of 17% protein (control) or 6% protein [low (LP) protein]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
47
1
13

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 29 publications
17
47
1
13
Order By: Relevance
“…The present animal model matches all hormonal, biochemical and phenotypic characteristics of those reported in previously published studies (Latorraca et al 1998, Prada et al 2001. The pancreatic islets of protein-deficient rats are smaller and possess fewer insulin granules than islets from eutrophic rats (not shown).…”
Section: Figuresupporting
confidence: 90%
See 1 more Smart Citation
“…The present animal model matches all hormonal, biochemical and phenotypic characteristics of those reported in previously published studies (Latorraca et al 1998, Prada et al 2001. The pancreatic islets of protein-deficient rats are smaller and possess fewer insulin granules than islets from eutrophic rats (not shown).…”
Section: Figuresupporting
confidence: 90%
“…Several studies have attempted to characterize the molecular mechanisms underlying the impaired response of the pancreatic islets of protein-deficient animals to glucose and other insulinotrophic agents (Rao & Menon 1993, Reis et al 1997, Latorraca et al 1998, Barbosa et al 2002, Ferreira et al 2003. Caloric and protein deficiency produce phenotypic changes in pancreatic islets, which are smaller and composed of a lower number of -cells, than islets of eutrophic animals (Petrik et al 2001).…”
Section: Figurementioning
confidence: 99%
“…Escriva et al (1991) observed the body weight gain reduction associated with functional alterations in insulin action in tissues in young rats subjected to protein restriction for four weeks. Latorraca et al (1998) evaluated the offspring of rats undernourished during pregnancy and breastfeeding. The animals exposed to a low protein diet had a reduction in insulin secretion, probably as a consequence of deficient Ca 2+ absorption in pancreatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of maternal malnutrition induced by either a low protein diet or caloric restriction during gestation and lactation cause major changes in the structure and function of several organs in the offspring. Pregnant rats fed a low protein diet produced pups with alterations in pancreatic islets (8,9). These include reduced islet vascularization, ␤ cell proliferative capacity, and islet size with rightward shift (decreased sensitivity) in glucose-stimulated insulin secretion and altered sensitivity to insulin in muscle (8,9).…”
Section: Evidence For Metabolic Programming In Animalsmentioning
confidence: 99%